Racismos: das Cruzadas ao Século XX - José Walter Silva e Silva; Gustavo Gonçalves Ungaro; Paula Anunciação Silva; Jane Alcina Prado da Silva; Wellington Camargo Fernandes (Universidade Nove de Julho, 2019)
Resenha do livro de Fernando Bethencourt: Racismos: das Cruzadas ao século XX